The functional impact of a rare germline TP53β N340D variant identified in breast cancer patients with the Li-Fraumeni-like syndrome - Christowitz, Claudia (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.